Assessment of landuse changes on soil organic carbon in the SBS Nagar district of Punjab using geospatial technology - SHRAMA, MANJU; RISHI, MADHURI; SETIA, R.; DIGRA, AMRITPAL; LOSHALI, D.C.; PATERIYA, BRIJENDRA (Journal of Soil and Water Conservation, 2023)
The analysis of past and present landuse/landcover (LULC) is important to understand about the interactions of human activities with the environment which is often used for planning and agricultural management purposes including soil organic carbon dynamics. Soil organic carbon (SOC) is a tool to fight climate change as the process of soil carbon sequestration takes CO2 out of the atmosphere and stores it in the soil in a stable form. The changes in LULC of the SBS Nagar of Punjab were studied using the Resourcesat-1 LISS-III satellite imageries for the years 2005-06 and 2015-16. The visual image interpretation technique was used to classify the satellite images and the area was classified into six classes: cropland, forest, plantation, wasteland (including scrubland), water bodies and settlements. Soil samples (0-30 cm) were collected from cropland, forest, wasteland, and plantation. These samples were analyzed for organic carbon using the standard method. During the period from 2005-06 to 2015- 16, area under cropland and wasteland was decreased but the area under settlement, forest, plantation and water bodies was increased. The average organic carbon content in soils was highest in forest (28 t C ha-1) followed by wasteland (26.7 t C ha-1), plantation (24.8 t C ha-1) and cropland (20.7 t C ha-1). Spatial variations in SOC content under different landuses of the study area showed that the content of organic carbon was decreased from east to western direction of the study area. Based on the assumption of equilibrium SOC, forest and plantation had positive effect on carbon sequestration in soils, but carbon was lost from cropland and wasteland soils over a period of 10 years.